2015
DOI: 10.1007/s11032-015-0264-y
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide association mapping of agronomic traits and carbon isotope discrimination in a worldwide germplasm collection of spring wheat using SNP markers

Abstract: Association mapping has been proposed to identify polymorphisms involved in phenotypic variations and may prove useful in identifying interesting alleles for breeding purposes. Using this approach, a total of 382 cultivars and advanced lines of spring wheat obtained from three breeding programs (Chile, Uruguay and CIMMYT) were evaluated for plant height (PH), kernels per spike (KS), 1,000 kernel weight (TKW), grain yield and carbon isotope discrimination (D 13 C) and tested for genotyping-bysequencing-derived … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
35
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(43 citation statements)
references
References 59 publications
6
35
1
1
Order By: Relevance
“…In this study, LD extent varied across chromosomes, from 0.55 cM for chromosome 7A to 12.84 cM for chromosome 1D (Table S4). The whole genome average critical r 2 value was 0.21, which is similar to the values reported by Mora et al (2015) and Edae et al (2014) in their spring wheat mapping panels. In this study, r 2 values varied from 0.17 for chromosome 3D to 0.27 for chromosome 5D.…”
Section: Resultssupporting
confidence: 88%
“…In this study, LD extent varied across chromosomes, from 0.55 cM for chromosome 7A to 12.84 cM for chromosome 1D (Table S4). The whole genome average critical r 2 value was 0.21, which is similar to the values reported by Mora et al (2015) and Edae et al (2014) in their spring wheat mapping panels. In this study, r 2 values varied from 0.17 for chromosome 3D to 0.27 for chromosome 5D.…”
Section: Resultssupporting
confidence: 88%
“…Genotypic differences for CID have been reported in numerous crop species including B. napus (Matus et al 1995;Chen et al 2011;Kottmann et al 2014;Dhanapal et al 2015;Mora et al 2015). Easlon et al (2013) demonstrated a relationship between CID and water-use efficiency in Arabidopsis; however, given the absence of any relationship between yield and CID in either the control or heat-stress treatment in this study, further exploration into the relationship of CID to heat stress appears unwarranted.…”
Section: Discussionmentioning
confidence: 67%
“…(Felsenstein 1989). Principal coordinate analysis was based on standardized covariance of genetic distances calculated for codominant markers (option DISTANCE, sub-option GENETIC), according to Mora et al (2015). Nei's genetic distances between inbred lines were used to create the UPGMA dendrogram, and their reliability was assessed by bootstrapping.…”
Section: Methodsmentioning
confidence: 99%